Relevance of Law Consumer Protection on Aircraft Post Master Flight Agent - Fitri Pratiwi Rasyid (Musamus Law Review, 2019)
At the time of the accident on the Lion Air flight JT 610, there were many ideas to close the flight operating permit. In fact, if reviewed further, for whatever reason, in some "corners", there are other rights that have not even received legal certainty about their protection. One of them is about airline ticket agents. Basically, according to the Consumer Protection Act, protection is not only given to consumers but businesses are also included in carrying out their trading activities. Business actors reach up to the airline agents. Moreover, before having a ticket sales permit, the agent must make a deposit to the airline ticket being sold. However, the protection that should be given in the laws and regulations does not explain the airline's obligation to return deposits to travel agents, who are likely to suffer fatal losses.